Validity of an Interactive STEM-Based E-Book on Science Material to Train Students Digital Literacy Skills - Firdatus Sukma Fitri Shiyamsyah; Sabar; Refni Adesia Pradiarti (Mataram University, 2026)
Digital technology development requires prospective elementary school teachers to possess adequate digital literacy competencies to design twenty-first-century learning effectively. One learning medium that can facilitate this competency is an interactive electronic book integrating Science, Technology, Engineering, and Mathematics (STEM). This study aimed to describe the validity of a STEM-based interactive e-book on science learning designed to foster digital literacy skills among undergraduate students. The study employed a Research and Development (R&D) approach using the Four-D (4D) development model consisting of Define, Design, Develop, and Disseminate stages. This article focuses on the Develop stage, particularly expert validation. Validation data were collected using material and media validation sheets with a four-point rating scale. Data were analyzed descriptively by calculating the average score for each validation aspect. The results indicated that the interactive e-book achieved an average score of 3.89 from the material expert, categorized as very valid, while the media expert evaluation resulted in an average score of 3.44, also categorized as very valid. The highest scores were obtained in material suitability, completeness, and language quality, while the media aspects demonstrated excellent visual design, interactivity, usability, and STEM integration. Therefore, the developed STEM-based interactive e-book is considered feasible for use as a learning medium to foster digital literacy skills among prospective elementary school teachers